Simplified method for purifying full-length major type IV pilins: PilA from Acidithiobacillus thiooxidans - Edgar D. Páez-Pérez; Araceli Hernández-Sánchez; Elvia Alfaro-Saldaña; J. Viridiana García-Meza (MethodsX)
Type IV major pilins are membrane-associated proteins that play critical roles in bacterial adaptation and survival across diverse environmental conditions, including potentially extreme ones. However, their expression and purification remain challenging due to their hydrophobic nature and tendency to aggregate. Here, we present a cost-effective method for the production and purification of recombinant full-length PilA, the major type IV pilin from the acidophilic bacterium Acidithiobacillus thiooxidans. By expressing the protein as a thioredoxin (Trx) fusion in Escherichia coli and using detergent-based solubilization combined with manual nickel affinity chromatography and spin-column anion exchange, we obtained stable and well folded protein suitable for downstream biophysical assays. Our approach eliminates the need for sophisticated FPLC systems and high-end chromatography columns, making it accessible to laboratories with limited resources. Structural stability of the purified protein was validated through intrinsic fluorescence spectroscopy under varying pH and denaturing conditions. This method can be readily adapted for the production of pilins from extremophilic and other pathogenic bacteria, providing a valuable tool for biotechnological and biomedical applications. • Enables purification of full-length pilins without requiring FPLC or high-cost columns • Applicable to the expression and analysis of structurally challenging pilins • Produces material suitable for biophysical studies, including fluorescence-based assays and structural analyses